Sheep Breeders’ Response to the Use of Papaya Seed Meal as a Natural Anthelmintic in Sriwedari Village Muntilan Subdistrict Magelang Regency - Muzizat Akbarrizki; Muhammad Louise; Akimi Akimi (SENTRI: Jurnal Riset Ilmiah, 2025)
This research was carried out in Sriwedari Village, Muntilan District, Magelang Regency, from May 10 to June 10, 2025. The purpose of the study was to determine the response of farmers to the use of papaya seed flour as a dewormer in sheep and to analyze the relationship between this response and the characteristics of farmers, including age, education level, and experience in livestock farming. This study used a Pre-test-Post test research design (One Group Pre-test Post-test Design) with a sample of 33 people selected using the purposive sampling method. The respondents' criteria were to have a minimum of seven sheep and more than 2 years of livestock experience. Data collection techniques include interviews, observations, documentation, and recording. Data analysis used descriptive analysis to determine the response of breeders and statistical analysis of Spearman's rank correlation to determine the relationship between respondent characteristics and responses. The variables studied consisted of independent variables, namely the characteristics of the breeder (age, education level, and experience in breeding) and the dependent variable (bound), namely the response of the breeder. The results of the study showed that the response of farmers to the use of papaya seed flour as a dewormer in sheep was in the very high category. The effectiveness of counseling is considered very effective, while the effectiveness of behavior change is categorized as effective. Statistical analysis showed that the variables of age and experience of breeding were not significantly related to the response of the breeders. Meanwhile, the education level variable has a very strong, positive, and significant relationship with farmers' responses.